Etnomatemática e educação matemática crítica: conexões teóricas e práticas - Caroline Mendes dos Passos (2008)
Searching for the true worth of the ways to know and to interpret different cultural groups reality (DAMBROSIO, 2001) and intending to insert the discussions, inside the classroom, related to the roles performed by Mathematics in the society (SKOVSMOSE, 1994), these are, respectively, Ethnomathematics and Critical Mathematics Educations main purposes. This work aims to point out the connections between these two perspectives and it was accomplished by two approaches: theoretical and practical. The practical study took place from observing Mathematics classes in a school in Belo Horizonte. The theoretical study looked for the connections mentioned above, researching these perspectives historic roots, their concepts and the distinguishing attributes that enable to the pedagogical practices. The connections pointed out in the theoretical study guided the analyze of the observed situations during the practical stage. Such analyze happened by the arrangement of feasible imagined situations to the two current situations chosen to take part in the dissertation. From this perspective of analyze, it was possible to put into practice what is named by Skovsmose and Borba (2004) as the act of surveying what is not the case, that is, one can imagine other actions and interplays that may be present in the education context, approaching both Ethnomathematics and Critical Mathematics Education aspects. The outcomes of the research showed that it is possible to develop a pedagogical practice that values the aspects of those two perspectives. Furthermore, the outcomes directed to a better understanding towards the Pedagogical Perspective of Ethnomathematics and toward the utilization of the concepts brought by the Critical Mathematics Education in the classroom, taking in this process as a result of an attitude, set by the teacher, which interferes in the actions (and reactions) of all subjects involved in the educational process.